Building Skills and Resources for Genomics, Epigenetics, and Bioinformatics Research for Africa: Report of the Joint 11th Conference of the African Society of Human Genetics and 12th H3Africa Consortium, 2018 - (:unkn) unknown (My University, 2020)
The 11th Congress of the African Society of Human Genetics (AfSHG) was held from September 16, 2018 to September 21, 2018, in conjunction with the 12th Human Heredity and Health in Africa (H3Africa) Consortium meeting in Kigali, Rwanda. The event was organized by the AfSHG in partnership with the Rwanda Society of Human Genetics and the University of Rwanda. A 2-day workshop on the application of next-generation sequencing technologies for analyzing monogenic disease in African populations was organized as part of the conference (September 22, 2018-September 23, 2018, Kigali, Rwanda). The theme of the conference was "Building skills and resources for genomics, epigenetics and bioinformatics research for Africa." The conference served as a platform to bring together members from country-specific Societies of Human Genetics, including Rwanda, Cameroon, Democratic Republic of Congo, Egypt, Mali, Senegal, and South Africa, and included 435 delegates from 38 countries, including 29 African countries that attended the conference. A major topic of discussion was how to bridge the gap between the emerging knowledge on genomics and Omics in African populations. The importance of understanding the role of genetic variation in disease causation and susceptibility among Africans was a constant theme during the meeting, as was the need to develop research infrastructure and resources to enhance healthcare systems, so that they are not left behind in the genomic revolution. It was concluded that there is a need to inspire more African scientists to train and work as investigators, clinicians, and genetic counselors in the field of human genetics in Africa. Local investments, and South-South and South-North collaboration were identified as the key drivers for the successful implementation of research and development on the continent.
Keywords: African Research